Burden of viral gastroenteritis in children living in rural China: Population-based surveillance - Jin-Xia Wang; Hong-Lu Zhou; Zhao-Jun Mo; Song-Mei Wang; Zhi-Yong Hao; Yue Li; Shan-Shan Zhen; Can-Jing Zhang; Xin-Jiang Zhang; Jing-Chen Ma; Chao Qiu; Gan Zhao; et al. (International Journal of Infectious Diseases, 2020)
Background: Despite the considerable disease burden caused by the disease, rotavirus vaccine has not been introduced into routine national immunization schedule, and norovirus vaccines are being developed without a comprehensive understanding of gastroenteritis epidemiology. To bridge this knowledge gap, we investigated the disease burden of viral gastroenteritis in rural China. Methods: Between October 2011 and December 2013, population-based surveillance was conducted in Zhengding and Sanjiang counties in China. Stool samples were collected from children <5 years of age with diarrhea. All specimens were tested for rotaviruses, noroviruses, sapoviruses, enteric adenoviruses, and astroviruses. Results: The most common pathogen causing diarrhea was rotavirus (54.7 vs 45.6 cases/1,000 children/year in Zhengding and Sanjiang, respectively), followed by norovirus (28.4 vs 19.3 cases/1,000 children/year in Zhengding and Sanjiang, respectively). The highest incidence of these viruses was observed in children 6–18 months of age. Among the 5 viral pathogens, rotaviruses caused the most severe illness, followed by noroviruses. Conclusion: Rotavirus and norovirus are the 2 most important viral pathogens causing childhood diarrhea in both northern and southern China; they should be the major targets for viral gastroenteritis prevention strategies among children in China. Keywords: Norovirus, Rotavirus, Adenovirus, Astrovirus, Gastroenteritis, China